The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/bse.1823
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development and the Consumer: Exploring the Role of Carbon Labelling in Retail Supply Chains

Abstract: This empirical article contributes to the sustainable development debate by examining consumer responses to carbon labels within a real world context. Given the limitations of methodologies that use self‐reported or intended measures of purchasing behaviour, we use the loyalty card data of the largest supermarket retailer in the UK to measure the impact of carbon labels on sales by different consumer segments. The data show that the trial of carbon labels on supermarket own brand products has had no discernibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 74 publications
1
59
0
Order By: Relevance
“…This is indicated by the negative part-worth utility value of the original label (group 1). The message that is communicated by the label seems to be incomprehensible to the average consumer [13]. The two further labels tested in group 1 show positive part-worth utilities, although being relatively low.…”
Section: Carbon Footprint Labelling and Label Designmentioning
confidence: 88%
See 2 more Smart Citations
“…This is indicated by the negative part-worth utility value of the original label (group 1). The message that is communicated by the label seems to be incomprehensible to the average consumer [13]. The two further labels tested in group 1 show positive part-worth utilities, although being relatively low.…”
Section: Carbon Footprint Labelling and Label Designmentioning
confidence: 88%
“…Consumers are more likely to be influenced by the price or origin of the product at the point of sale. Research revealed that the interpretation of the carbon footprint label turned out to be too demanding for the average customer [1,2,13,14]. This is due to the difficulty of classifying abstract numbers of greenhouse gas emissions that are shown on the label.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most food processors depend critically on water, either as an ingredient or as a requirement for the hygienic operation of their facilities, and water supplies have the potential to be impacted significantly by climate change in some regions. In addition, some downstream stakeholders and consumers are becoming increasingly concerned about the greenhouse gas (GHG) emissions associated with the food system [10][11][12][13] and this has the potential to influence future supply chain relationships and green market segments. These are among the reasons why climate adaptation strategies are needed in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Motives for reporting vary based on a variety of drivers including retailer and brand pull of manufacturers [3][4][5][6] shareholder interest in corporate social responsibility [7][8][9] desire to improve community relations [10], or to attract/retain high skilled employees that care about the environment [11]. Among the many papers on -why-companies report, Aras and Crowther [12] present the notion that reporting is more about convincing the investment community that the corporation doing the reporting is less risky, thereby reducing the cost of capital.…”
Section: Introductionmentioning
confidence: 99%